The Integration of Socioemotional Learning in the University Curriculum: a Challenge for Innovation - Salas-Hernández, José Isaías (2023)
Introduction: This study seeks to analyze the issue of the integration of socioemotional learning in the development of engineering career curricula. Objective: To analyze the manifestations of the problem of integration of socioemotional learning in engineering curricula, from the perspective of the actors of a private Colombian university. Method: A semi-structured questionnaire was applied to 20 informants from the student body and faculty of the engineering career, management and administrative staff. The responses were coded and contrasted with approaches in the literature for categorization and inference. Results: several factors, among them the lack of knowledge about socioemotional learning and the scarce participation of the actors in curricular processes, prevent the effective integration of such learning. Discussion: The integration of SEL requires the participation of the different university actors in the deliberation, design, testing and evaluation of meaningful practices from action research.